Perubahan Sosial Budaya, Lingkungan Hidup Serta Persepsi Masyarakat Sekitar Lokasi Perkebunan Kelapa Sawit Di Kabupaten Barito Kuala Propinsi Kalimantan Selatan. (Studi Kasus Di Desa Karya Jadi Kecamatan Tabukan) - Adenansi, Adenansi (Rawa Sains: Jurnal Sains STIPER Amuntai, 2023)
This research aims to find out. This research aims to find out how the social and cultural impacts, as well as the environment (swamp land and natural forest and agriculture) that occur after the operation of oil palm plantation companies in Batola Regency. This type of research is a qualitative research (survey) with a case study approach. Respondents in this study were residents of Karya Jadi Village, Tabukan District, Batola Regency. Respondents were selected by purposive sampling method as many as 31 respondents, the sampling technique was based on a specific purpose (the selected person actually has criteria as a sample) with the criteria that is, residents who have lived in the village for a long time have lived in the village since 2006, living in the village continuously in the sense of never leaving the village for a long time, having a job as a farmer, employee of an oil palm plantation company, business actors (traders, fish seekers, galam seekers and others).